Pengalaman Keluarga dalam Membantu Aktivitas Fisik Pasien Chronic Kidney Disease (CKD) yang Menjalani Hemodialisis - Resmi Pangaribuan; Ermi Girsang; Elis Anggeria (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
Chronic Kidney Disease (CKD) is a growing global health problem. Patients undergoing hemodialysis frequently experience decreased physical capacity, fatigue, and limitations in daily activities. Physical activity has proven physiological and psychological benefits; however, its implementation largely depends on family support as primary caregivers. To date, limited studies have deeply explored family experiences in supporting physical activity among hemodialysis patients in the Indonesian healthcare context. To explore and gain an in-depth understanding of family experiences in supporting physical activity among CKD patients undergoing hemodialysis. A qualitative study with a phenomenological approach was conducted at Tk. II Putri Hijau Hospital Medan in September 2025. Ten family members were recruited using purposive sampling based on inclusion criteria. Data were collected through semi-structured in-depth interviews and analyzed using thematic. Analysis based on Colaizzi’s approach. Trustworthiness was ensured through source and method triangulation, member checking, and audit trail. Six major themes emerged: (1) the meaning of physical activity in patient recovery, (2) family support during hemodialysis sessions, (3) simple home-based physical activities, (4) physical and psychological barriers, (5) emotional burden of caregivers, and (6) the importance of healthcare professional education. Families played an active role in motivating, assisting, and adapting physical activities to patients’ conditions. Family experiences indicate that emotional, motivational, and educational support are key factors in promoting physical activity among hemodialysis patients. These findings highlight the importance of family-centered nursing interventions in CKD rehabilitation programs.